Comparative study of outcomes of type-1 tympanoplasty with temporalis fascia only and with cartilage slice reinforcement - Rathaur, Shiv Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Tympanoplasty is a surgical procedure performed to eradicate infection and restore the function of middle ear. Cartilage slice support offers an extremely reliable method for reconstruction of tympanic membrane in cases of high-risk perforation. The purpose of this study was to evaluate the graft uptake and auditory outcomes of type I tympanoplasty using temporalis muscle fascia only and with cartilage slice reinforcement. Methods: This prospective study was conducted at the Department of Otorhinolaryngology, Government Medical College, Jalaun, Uttar Pradesh, India from November 2016 to November 2019. There were total of 100 patients, divided in two groups, 50 patients in each group, tympanoplasty type-1 using only temporalis fascia (group-A) and tympanoplasty type-1 using temporalis fascia with cartilage slice reinforcement (group-B). The result was measured on graft uptake and hearing outcome at 6 months postoperatively. Results: Overall graft uptake rate in group-A was 94%, whereas that in group-B was 100%. The age and sex had no significant effect on the success rate of surgery (p>0.05) in group-A. The average air bone gap (ABG) decreased from 28.3 dB to 10 dB, in group-B, the average ABG was 28.3 dB preoperatively and reached 16.6 dB after surgery. The difference between the rates of ABG improvement in the two groups was significant (p<0.01). Conclusions: Hearing improvements is better in tympanoplasty type-1 with a temporalis graft only then with cartilage slice reinforcement. However, the graft uptake rate is higher in cartilage reinforcement compare with temporalis muscle fascia only.